Model Sosialisasi Internalisasi Norma Sosial Berlalu Lintas Remaja Pengguna Sepeda Motor - Dwiyanti Hanandini; Wahyu Pramono (Jurnal Administrasi Publik dan Pemerintahan, 2023)
Until june 2017 the number of a traffic violation in the city the has reached 11.816 cases. The condition 2017, has actually not in contrast to the conditions a traffic violation on 2016 namely 26.267 cases. A motor vehicle that do a lot of violence and had an accident traffic is a motorcycle. Meanwhile, teenagers is the most numerous group violations and had an accident traffic compared with adults. A traffic violation among teenagers largely caused by teenager have not been able to change the rules about knowledge and has become moral behaviour in performs traffic. Traffic accidents always starts with the offense the traffic signs. Socialization and internalization traffic regulation among teenagers be important to be done to make the knowledge which has created you teenagers about traffic can be means of control from the inside as well as the operation of young people in traffic. Socialization need is employed to impart media have the same social values that which is embraced by the community. The selection of media for the socialization that will exactly can produce the process that internalization efektf for individuals. Social media, the internet be a pleasant that is very much a reference for youth in understanding but social norm